Pengaruh Penambahan Ubi Jalar Ungu (Ipomoea batatas L) Terhadap Organoleptik Dan Kadar Antosianin Klepon - Sari, Maulida; Sari, Mella Mutika; Irhasyuarna, Yudha (CV.ITTC INDONESIA, 2024)
ABSRACT The method of processing klepon generally hereditary and very few people create klepon. Efforts are being made to enrich the nutritional content of klepon and reduce the use of glutinous rice flour in making klepon, by adding purple sweet potato. This study aims to: (1) Determine the panelists' acceptance of klepon with the addition of purple sweet potato, (2) Determine the anthocyanin levels of klepon with the addition of purple sweet potato. This type of research is experimental. The method used was Completely Randomized Design (RAL) with four treatments of adding purple sweet potato to klepon, namely 0% ; 60% ; 50% ; 40%. The organoleptic test data collection technique used a questionnaire on 25 untrained panelists. The results of the statistical analysis of the Kruskal Wallis test obtained color (p = 0.350), scent (p = 0.001), texture (p = 0.016), taste (p = 0.014). The results of the One-Way ANOVA statistical analysis showed anthocyanin levels (p = 0.001). The results showed that the F1 product was the best product in terms of color. Product F0 is the best product in terms of scent. Product F2 is the best product in terms of texture and taste. Overall product F2 is the best product with the highest average value of 3.78. While product F1 is a product that has the highest average value of anthocyanin content of 0.9719 mg/100 g.